Distribution, sources, and fluxes of heavy metals in the Pearl River Delta, South China. Issue 2 (30th December 2015) - Geng, Junjie; Wang, Yiping; Luo, Hanjin
Abstract: Riverine samples were collected at various locations in the Pearl River Delta (PRD) to determine the concentrations of heavy metals (Cr, Ni, Cu, Mn, Zn, Cd, and Pb) in time and space and to estimate the fluxes of heavy metals to the coastal waters off South China. Most of the elements exhibit clear temporal and spatial trends. Principal component analysis shows that surface erosion is the major factor affecting metal concentrations in particulates in the PRD. Natural geology is an important source of these heavy metals. The annual fluxes of Cr, Ni, Cu, Mn, Zn, Cd, and Pb in upstream and downstream were 445, 256, 241, 3293, 1279, 12, and 317 t/year and 1823, 1144, 1786, 15, 634, 6183, 74, and 2017 t/year, respectively. A comparison indicated that the annual fluxes of Mn accounted for 1.3% of the global river fluxes, whereas other elements contribute < 1%. Highlights: The temporal and spatial variability of heavy metals in the Pearl River Delta (PRD), China, was analyzed. Natural geology is a common factor influencing heavy metal concentrations throughout the PRD region. The fluxes of heavy metals of the Pearl River were calculated. The output fluxes of the target metals to the global rivers were quantified.